L-arginine abrogates salt-sensitive hypertension in Dahl/Rapp rats. - Chen, P Y; Sanders, P W (The Journal of Clinical Investigation, 1991)
This study examined the contribution of nitric oxide (NO) to the susceptibility or resistance to the hypertensive effects of high sodium chloride (8.0% NaCl) intake in young Dahl/Rapp salt-sensitive (SS/Jr) and salt-resistant (SR/Jr) rats. Using NG-monomethyl-L-arginine (L-NMMA) as a probe for NO production in vivo, we found that increasing dietary sodium chloride increased NO activity in salt-resistant rats, but not in salt-sensitive rats. Exogenous L-arginine, the substrate for NO synthesis, decreased blood pressure to normotensive levels in salt-sensitive rats made hypertensive for 2 wk from 8.0% NaCl chow. D-arginine had no effect on blood pressure of these rats and L-arginine did not change blood pressure of salt-resistant rats. Intraperitoneal injections of L-arginine and its precursor, L-citrulline, and oral L-arginine, but not D-arginine, prevented the increase in blood pressure in salt-sensitive rats on the high salt chow over 2 wk of observation. In contrast, L-arginine did not alter the development of hypertension in spontaneously hypertensive rats. Mean urinary cGMP levels were higher in salt-sensitive rats on oral L-arginine than salt-sensitive rats on D-arginine. Infusion of L-NMMA acutely decreased, whereas intravenous L-arginine rapidly increased, urinary cGMP in both groups. L-arginine and L-citrulline increased production of NO and prevented salt-sensitive hypertension in Dahl/Rapp rats. Images